2008
DOI: 10.1111/j.1525-1594.2008.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Biocompatibility of Lyophilized Bovine Pericardium Implanted Subcutaneously in Rats

Abstract: This article aims at investigating in vivo evaluation of lyophilization procedure on the biocompatibility of bovine pericardium treated with glutaraldehyde (GA). The bovine pericardium was fixed with 0.5% glutaraldehyde during 10 days and preserved in 4% formaldehyde (FA). Two groups of samples were prepared from treated membranes: Group 1, nonlyophilized samples and Group 2, lyophilized samples. Male Sprague-Dawley rats (4 weeks after birth) were anesthetized (pentobarbital sodium 25 mg/kg of body weight) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…The bovine collagen part, which is biological in its origin, can be digested by inflammatory cells and collagenases, like other collagenous tissues, and with time suffers cartilaginous metaplasia (Wolley, 1984;Schlosser et al, 2005). The degradation of bovine pericardium is retarded by glutaraldehyde treatment, and it is not changed by lyophilization, (Laun et al, 1990;Maizato et al, 2003;Zuki et al, 2007;Maizato et al, 2008). They also found that lyophilization decreases the inflammatory response.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The bovine collagen part, which is biological in its origin, can be digested by inflammatory cells and collagenases, like other collagenous tissues, and with time suffers cartilaginous metaplasia (Wolley, 1984;Schlosser et al, 2005). The degradation of bovine pericardium is retarded by glutaraldehyde treatment, and it is not changed by lyophilization, (Laun et al, 1990;Maizato et al, 2003;Zuki et al, 2007;Maizato et al, 2008). They also found that lyophilization decreases the inflammatory response.…”
Section: Discussionmentioning
confidence: 84%
“…Lyophilization has been used to decrease aldehyde residues in GPBP, hence decreasing cytotoxicity and enhancing resistance to calcification (Maizato et al, 2003). The lyophilized glutaraldehyde preserved bovine pericardium (LGPBP) has been tested in vitro (Maizato et al, 2003), in non anatomical lung resection (OlmosZúñiga et al, 2001), as a dural substitute (Laun et al, 1990), abdominal wall repair (Olmos-Zúñiga et al, 1996, Zuki et al, 2007 and subcutaneous implantation (Maizato et al, 2008), with good results, nevertheless in all these works the LGPBP was implanted outside the cardiovascular system, and the main factor for GPBP degradation is the contact with host blood, as well as the site of implantation and function (Pires et al, 1999;Gabbay et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The use of glutaraldehyde preserved bovine pericardium (GPBP) and lyophilized bovine pericardium can overcome these issues. Glutaraldehyde treatment decreases the antigenicity of pericardium, delaying the digestion by inflammatory cells [54], and lyophilization decreases aldehyde residues in GPBP, hence decreasing cytotoxicity and enhancing resistance to calcification [55,56].…”
Section: Naturally Derived Polymersmentioning
confidence: 99%
“…The histopathological characteristics of the inflammatory infiltrate were made according to the methodology described by Maizato et al 20 , which include the analysis of the presence of granulomatous reaction, mononuclear infiltrate, granulomatous tissue, necrotic tissue and bacteria. Quantification was based on the percentile extension seen in the microscopic fields and graded from 0 to 4 as follows:…”
Section: Histomorphological Analysismentioning
confidence: 99%